Quaternionic quantum Turing machines - Dai, Songsong (Frontiers in Physics, 2023)
Quaternionic quantum theory is an extension of the standard complex quantum theory. Inspired by this, we study the quaternionic quantum computation using quaternions. We first develop a theory of quaternionic quantum Turing machines as a model of quaternionic quantum computation. Quaternionic quantum Turing machine also can be seen as a generalization of complex quantum Turing machine. Then we introduce weighted sum of quaternionic quantum Turing machines and establish some of basic properties.